Eveningness chronotype and depressive affective temperament associated with higher high-sensitivity C-Reactive Protein in Unipolar and Bipolar Depression - L. Orsolini; S. Pompili; A. Cicolini; L. Ricci; U. Volpe (European Psychiatry, 2023)
Introduction Several studies investigated the role of inflammation in the etiopathogenesis of psychiatric disorders, by also evaluating how CRP may exert a pathoplastic and/or psychopatological role in mood disorders. Objectives The aim of our cross-sectional study is evaluating the high-sensitivity C-reactive-protein (hsCRP) levels in a cohort of unipolar and bipolar depressive inpatients, in relation with psychopathological, temperamental and chronotype features. Methods Among 313 screened inpatients, we recruited 133 moderate-to-severe depressive patients who were assessed for hsCRP levels, chronotype with Morningness-Eveningness Questionnaire (MEQ) and affective temperament with Temperament Evaluation of Memphis, Pisa, Paris and San Diego (TEMPS). Results hsCRP levels were significantly higher among those with previous suicide attempt (p=0.05), death (p=0.018) and self-harm/self-injury thoughts (p=0.011). In addition, hsCRP levels were significantly higher among patients with hypertension (p=0.020) and dyslipidemia (p=0.013). Moreover, positive correlation were found between hsCRP levels and the number of illness of years (p<0.001). Significant positive correlation were found between hsCRP levels and depressive (p<0.001) and cyclothymic (p<0.001) affective temperaments, while a negative correlations were reported between hsCRP levels and hypertimic (p<0.001) and irritable (p=0.029) affective temperaments. Eveningness chronotypes subject displayed higher hsCRP levels compared to intermediate-type and morningness-type chronotypes (p<0.001). Linear regression analyses, adjusted for all covariates, demonstrated that higher scores at the TEMPS-M depressive, while lower scores at the hyperthymic and irritable affective temperaments [F=88.955, R2=0.710, p<0.001] and lower MEQ scores [F=75.456, R2=0.405, p<0.001] statistically significantly predicted higher hsCRP. Conclusions Eveningness chronotype and a depressive affective temperament appeared to be associated with higher hsCRP levels during moderate-to-severe unipolar and bipolar depression. Further longitudinal and larger studies should better characterise patients with mood disorders by investigating the influence of chronotype and temperament. Disclosure of Interest None Declared